INTRAVASCULAR LEIOMYOMATOSIS WITH GREAT VESSELS EXTENSION - Fonseca Villanea, Carlos; Borbón Cordero, María Fernanda; Molina Mainieri, Silvia; Goyenaga Castro, Pablo; Jiménez Juárez, Roger (Revista Médica de la Universidad de Costa Rica, 2019)
The intravascular leiomyomatosis is a rare pathology, described as a non malicious proliferation generally composed for smooth muscle cells originated from the uterus vein walls, this mass has the ability to invade gonadal, iliac and renal veins until the inferior cava vein, in some exceptional cases it could reach the right heart cavities, causing an embolic or obstructive pathology. Due to its low incidence and few reported cases, the management of the intravascular leiomyomatosis produces confusion on its diagnostic and treatment. A clinical case is presented of a 36 years old female, who consults the emergency services presenting an abdominal pain, diarrheic depositions and low orally tolerance, associated to edema in lower members. The patient has background of a six-month prior hysterectomy with left salpingo-oophorectomy. Using an abdominal echography, computerized angiotomography, and the transthoracic ultrasound, it was checked the presence of a tumoral mass that invaded the iliac veins, left renal, inferior cava vein, until it reached the right heart cavities. A two-time surgical management was decided. The post-surgical pathology assessment determined the diagnostic of the intravascular leiomyomatosis with extension to great vessels.